Wybrane zagadnienia rozwoju systemu prawno-instytucjonalnego ochrony i eksploatacji środowiska przyrodniczego w Polsce od powstania państwa do II wojny światowej - Becla, Agnieszka (Some chosen problems of developing the law-institutional conservation and exploitation of environmental system on the Polish land since the rise of the to Word War II, 2007)
The article presents some chosen problems of developing the environmental law system and its institutions in Poland to 1945. It presents different, changing regulations - both law norms and institutions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 15-23,